Klasifikasi Penyakit HepatitisC Menggunakan Algoritma Support Vector Machine - Ni Kadek Trisnawati; I Gede Santi Astawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Hepatitis is an inflammation of the liver which is often caused by a virus. Hepatitis that lasts less than 6 months is called